Finding Thea [videorecording (DVD)] - Haley, Nancy Bourne; Ostrander, Lucy (LUNA, 2006)
Although her name is found on a waterway, a park and other places in Tacoma, Thea Foss' personal story is not well known. An immigrant from Norway and a pioneer business woman, she founded, with her husband, the Foss Launch Company. This small venture grew to be the Foss Launch and Tug Company, and is now the Seattle-based Foss Maritime Company, reputedly the largest tugboat company on the West Coast. The Tugboat Annie character made popular in the 1930s in short stories and several films was very loosely based on Thea Foss, caricaturing the strong and independent spirit of a woman otherwise nothing like the film character.